The last thing I remember / Andrew Klavan - Klavan, Andrew
High school student Charlie West awakens bloody and bruised in a concrete bunker, only to discover that he has lost a year of his life and remembers nothing about escaping from prison after being convicted of murdering his former best friend, or why he is being pursued by both the law and a group of terrorists trying to bring down the government of the United States.